2016
DOI: 10.1016/j.jvs.2016.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Low-profile versus standard-profile multibranched thoracoabdominal aortic stent grafts

Abstract: LPSGs had similar safety profile and midterm outcomes compared with the SPSGs for treatment of pararenal and TAAA. The substitution of LPSGs for SPSGs lowered the number of patients who required conduit insertion to avoid access artery injury, especially in women, thereby reducing an otherwise striking gender difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Four studies did not make a statement about the severity of the event but reported that four patients with a cerebrovascular accident did fully recover, one patient recovered moderately and one patient did not recover at all [12,23,25,27]. One article did not make a statement about the clinical severity or the recovery [26]. Four studies included in the review reporting cerebrovascular events did not mention the affected brain territory nor the patient's clinical symptoms [11,19,22,23].…”
Section: Results Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies did not make a statement about the severity of the event but reported that four patients with a cerebrovascular accident did fully recover, one patient recovered moderately and one patient did not recover at all [12,23,25,27]. One article did not make a statement about the clinical severity or the recovery [26]. Four studies included in the review reporting cerebrovascular events did not mention the affected brain territory nor the patient's clinical symptoms [11,19,22,23].…”
Section: Results Of the Included Studiesmentioning
confidence: 99%
“…Aneurysm extent included 262 thoracoabdominal aortic aneurysms [10,11,21,[27][28][29] and 867 complex (from juxtarenal to paravisceral) abdominal aortic aneurysms [10-12, 16, 18-20, 23-25, 27, 28]. Two studies did not provide aneurysm classification [22,26]. The mean diameter was reported by seven studies and ranged from 50 mm to 74 mm, and the overall mean diameter was 64 mm [11,18,19,[23][24][25].…”
Section: Patient Demographics and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Low profile stent grafts increase the applicability of b-EVAR with comparable outcomes to the standard profile version. 7,17 Striving for good long-term results has changed some of the authors' practices. Any bridging stent is liberally reinforced whenever it might be jeopardised within a small or angulated aorta, or has to pass through a suprarenal bare stent of a previous infrarenal stent graft ( Fig.…”
Section: Discussionmentioning
confidence: 99%